A Targeted Release Capsule of Lanthanum Carbonate: a New Efficient Cheap Treatment for Primary Hyperoxalurias - Marc E. De Broe; Marc P. Uytterhoeven; Jan De Causmaecker; Yannick De Brucker; Erik D. Snelders; Johan Van De Walle; Koen Van Hoeck; Dominique Trouet; Monique Elseviers (Kidney International Reports)
Introduction: Primary hyperoxaluria (PH) is a devastating disease in children and adults. Recently, a substantial progress in the treatment of this deadly disease has been made that consists of the introduction of the RNA inhibitors, lumasiran and nedosiran, which deplete the substrate for oxalate synthesis. Methods: Lanthanum carbonate (Lanth.Carb., La2[CO3]3) is a powerful phosphate binder having a strong affinity to oxalate. Its use as such in PH is not relevant because patients with normal renal function develop a severe phosphate depletion without a clear effect on oxalate balance. Considering that the absorption of phosphate is in the early gastrointestinal (GI) tract and mainly in the distal part of the GI tract for oxalate, we developed a targeted release capsule (trc) containing 500 mg Lant.Carb. released in the distal part of the GI tract as proven by radiological investigations of the radiopaque trcLanth.Carb. Results: Four patients with PH and estimated glomerular filtration rate > 60 ml/min per 1.73 m2 were treated with trcLanth.Carb., which turned out to decrease the urinary oxalate concentrations clearly < 0.51 mmol/24 h per 1.73 m2,45 mg/24 h per 1.73 m2 (considered as upper limit of normal), after 2.5 months of treatment in 3 patients and 18 months in 1 patient. Calciuria remained normal or decreased slightly. Phosphaturia and phosphatemia remained normal and stable in all 4 cases. Conclusion: trcLanth.Carb. is a promising repurposed, efficient, nontoxic, and cheap drug, lacking serious side effects in the treatment of any type of PH in whatever place in the world. A randomized controlled trial supporting this proof-of-concept is the next step.